1. 4P + 5O2 (изб) = 2P2O5
2. P2O5 + 3H2O = 2H3PO4
3. H3PO4 + 3KOH = 3H2O + K3PO4
2H3PO4 + 6K = 2K3PO4 + 3H2
3K2O + 2H3PO4 = 3H2O + 2K3PO4
Р => P4O10 => H3PO4 => K3PO4
Объяснение:
1) 4P + 5O2 => P4O10
2) P4O10 + 6H2O => 4H3PO4
3) 2H3PO4 + 3K2O => 2K3PO4 + 3H2O
1. 4P + 5O2 (изб) = 2P2O5
2. P2O5 + 3H2O = 2H3PO4
3. H3PO4 + 3KOH = 3H2O + K3PO4
2H3PO4 + 6K = 2K3PO4 + 3H2
3K2O + 2H3PO4 = 3H2O + 2K3PO4
Р => P4O10 => H3PO4 => K3PO4
Объяснение:
1) 4P + 5O2 => P4O10
2) P4O10 + 6H2O => 4H3PO4
3) 2H3PO4 + 3K2O => 2K3PO4 + 3H2O